Molecular detection of hemogregarines and haemosporidians in Brazilian free-living testudines - Oliveira, Juliana Paula de [UNESP]; André, Marcos Rogério [UNESP]; Alves Júnior, José Roberto Ferreira; Lustosa, Ana Paula Gomes; Werther, Karin [UNESP] (Elsevier, 2018)
Morphological and molecular techniques were used to investigate the presence of hemogregarines and haemosporidians in biological samples of free-living Geoffroy's side-necked turtles (Phrynops geoffroanus) and Giant Amazon turtles (Podocnemis expansa) from Brazil. No evolutionary form of haemosporidians or hemogregarines were observed in the blood smears of 83 P. geoffroanus samples, and there were no meronts in the histological sections of 31 necropsied P. geoffroanus samples. All DNA samples extracted from P. geoffroanus tissues and blood aliquots were negative in haemosporidian PCR assays (based on the mitochondrial cytochrome b gene) and hemogregarine PCR assays (based on the 18S rRNA gene). In the analysis of blood smears of all seven Podocnemis expansa evaluated, gametocytes of hemogregarines were observed. The seven P. expansa were negative in the haemosporidian PCR assays. Moreover, hemogregarine DNA was detected in blood samples from all of the sampled P. expansa. The phylogenetic maximum likelihood inference and probabilistic Bayesian inference revealed five closely related genotypes that formed a monophyletic group. There was also a sister group to the lineage that consisted of Haemogregarina spp. of freshwater turtles from Canada, Italy, Mozambique, Kenya, Gabon, Vietnam, and China. The findings suggest that free-living P. expansa were parasitized by a new genotype or even a possible new species of the genus Haemogregarina. Haemosporidians and hemogregarines are not frequently found in P. geoffroanus in the studied region under the local conditions of that period.
Keywords: Haemogregarina; PCR; Phrynops geoffroanus; Phylogeny; Podocnemis expansa; Turtle